Open Loop Recycling of Recycled Polypropylene for Motorcycle Saddle Application - Wattanachai, Piyachat; Buasathain, Benjawan; Antonio, Christian; Roces, Susan (ASEAN Journal of Chemical Engineering, 2017)
This research investigated the possibility of using polymer blends of virgin and recycled polypropylene (PP) for a motorcycle saddle application. Three different recycled PPs obtained from different sources contained carbon black (CB). Specimens were prepared by injection molding for mechanical property testing and color characterization whereas scraps from runners were used for thermal property testing. It was found that tensile and flexural properties of recycled PPs were better than those of virgin PP due to the fact that recycled PPs contained CB which is a reinforcing material. These properties were improved as the amount of recycled PP added increased. Since recycled PPs are strong materials, they are hence brittle resulting in lowering impact strength and percent elongation. The recycled PP sources and compatibility between virgin and recycled PPs strongly influence the blends’ properties. The melt flow index of the blends increased as the amount of the recycled PP increased because of the short polymer chains of recycled PP resulting from earlier processing. Blending virgin PP with recycled PP not only improves its properties, but also reduces raw material costs in the range of 5-13%. The advantage of open loop recycling is a wider recycled plastic market.